2013
DOI: 10.1071/shv10n6ab6
|View full text |Cite
|
Sign up to set email alerts
|

6. Prevalence, genotype diversity and determinants of anal HPV infection in high-risk men attending a sexually transmitted infection clinic in Puerto Rico

Abstract: Background Recent studies in Puerto Rico (PR) have reported an increasing incidence of anal cancer in Puerto Rican men. The objective of this study was to determine the prevalence, genotype distribution and risk factors associated with anal HPV infection among heterosexual men and men who have sex with men (MSM) attending an STI clinic in PR. Methods: We conducted a cross-sectional study of men 18 years and older. A comprehensive survey was administered that included a demographic and behavioural assessment. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…97 Conversely, protective factors for HPV infection include CD4 count greater than 500, adherence with highly active antiretroviral therapy, and undetectable viral load. 98,99 The unique vulnerability of transgender women to both HIV infection and HPV-related disease warrants special attention. Because of commonalities in viral transmission mode, many of the risk factors for HIV acquisition in MSM and TGW extend to risk of HPV infection as well.…”
Section: Analmentioning
confidence: 99%
See 4 more Smart Citations
“…97 Conversely, protective factors for HPV infection include CD4 count greater than 500, adherence with highly active antiretroviral therapy, and undetectable viral load. 98,99 The unique vulnerability of transgender women to both HIV infection and HPV-related disease warrants special attention. Because of commonalities in viral transmission mode, many of the risk factors for HIV acquisition in MSM and TGW extend to risk of HPV infection as well.…”
Section: Analmentioning
confidence: 99%
“…123,154 Low HPV knowledge may be of a particular concern among diverse MSM and interestingly may cross geographic borders. Awareness of an HPV vaccine varied between 3% and 30% among ethnic minority MSM from Serbia, China, Puerto Rico, and the United States, 98,[155][156][157][158][159] and although low awareness was initially correlated with low willingness to receive the vaccine, this seems to be highly sensitive to education. 146,156,160 Importantly, while anal HPV is highly prevalent among TGW, Meites et al 86 demonstrated that only a minority (8%) of sexually active TGW will test positive for all HPV subtypes covered in the quadrivalent HPV vaccine, indicating that HPV vaccination would still have protective utility.…”
Section: Vaccinationmentioning
confidence: 99%
See 3 more Smart Citations